Generalized Structure of the Algorithm for Automated Detection of Non Relevant and Wrong Information on Web Resources - Dyvak, Mykola; Kovbasistyi, Andrii; Stakhiv, Petro; Lipiński, Piotr (Journal of Applied Computer Science, 2017)
In this article the algorithm for automated detection of non-relevant or wrong information on websites is introduced. The algorithm extracts the semantic information from the webpage using third party software and compares the semantic information with the reliable resources. Reliable information is identified by the means of majority voting or extracted from reliable databases